The Influence of Key Opinion Leaders (KOLs) on Consumer Purchase Interest of Student in Bandung, Indonesia - Saputra, Ramadhan; Chaniago, Harmon (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aimed to determine how Key Opinion Leaders (KOLs) influence student buying interest in Greater Bandung, Indonesia. Respondents in this study came from vocational students and university students in Greater Bandung who have used social media. This study uses a quantitative descriptive method using statistical analysis in the form of validity and reliability tests, simple linear regression tests, correlation tests, and normality tests. The sample in this study amounted to 115 respondents. The data collection technique used was distributing questionnaires to respondents via Google Forms. The results showed that key opinion leaders have a significant effect on buying interest, which means that key opinion leaders can influence the buying interest of students in Greater Bandung, Indonesia.